Semiprime RÎ“-Submodules of Multiplication RÎ“-Modules - Zyarah, Ali Abd Alhussein; Al-Mothafar, Nuhad Salim (Iraqi Journal of Science, 2020)
Let R be a Î“-ring and G be an RÎ“-module. A proper RÎ“-submodule S of G is said to be semiprime RÎ“-submodule if for any ideal I of a Î“-ring R and for any RÎ“-submodule A of G such that or which implies that . The purpose of this paper is to introduce interesting results of semiprime RÎ“-submodule of RÎ“-module which represents a generalization of semiprime submodules.